2020
DOI: 10.1016/j.jpeds.2020.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Routine Pediatric Practice in Light of Coronavirus 2019 (COVID-19)

Abstract: he outbreak of severe acute respiratory syndrome coronavirus 2 or coronavirus 2019 (COVID-19) 1 in the city of Wuhan, China, in December 2019 has rapidly emerged into a pandemic affecting national communities throughout the world. 2 As of May 17, 2020, more than 4.5 million people have been infected globally at a pace of 100 000/d, and 307 395 have died. 3 We will briefly discuss the effects of COVID-19 on routine pediatric practice that have surfaced during the months after the onset of the pandemic and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
1
39
0
6
Order By: Relevance
“…Monthly comparison of pediatric ED visits performed from January to May 2020 confirmed a significant reduction in daily consultations after February, with a considerable percentage of days with ≤ 3 visits/day ( Table 1). Daily pediatric ED consultations significantly varied also considering pre-and post-lockdown beginning period (pre-lockdown, 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)…”
Section: Impact Of Covid-19 Pandemic On Pediatric Ed Consultationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly comparison of pediatric ED visits performed from January to May 2020 confirmed a significant reduction in daily consultations after February, with a considerable percentage of days with ≤ 3 visits/day ( Table 1). Daily pediatric ED consultations significantly varied also considering pre-and post-lockdown beginning period (pre-lockdown, 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)…”
Section: Impact Of Covid-19 Pandemic On Pediatric Ed Consultationsmentioning
confidence: 99%
“…Phase 2 started on May 4th, 2020, and was characterized by progressive relaxation of containment measures allowing outdoor physical activity, opening of the public parks, and visits to relatives within the regional territory (always keeping the distance of at least 1 m and with the mandatory use of masks) [11,12]. These strategies caused a substantial decline in ED visit and hospitalizations [13,14]. Preliminary data from 5 Italian pediatric ED showed that, during lockdown (March 1st-27th, 2020), ED visits were significantly decreased (up to 88%) as compared with the same time period in 2018 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is the most common surgical emergency in children, and may present under several forms, such as uncomplicated appendicitis, or complicated appendicitis with either peritonitis or with appendiceal mass/abscess [ 7 ] . Although the cause for appendicitis remains poorly understood, we hypothesized that the COVID-19 outbreak may influence our practice regarding number of cases, management, and outcome of acute appendicitis for several reasons [ 8 ]. First of all, as most general pediatric surgery departments closed, only referral pediatric centers remained functional, and with more than 3 million children in the region of Paris, the number of patients referred to our center for appendicitis treatment may increase [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the global pandemic of COVID-19, many countries around the world adopted social isolation measures to contain the spread of the virus 1 . For children and adolescents, limitations in face-to-face activities and interactions with their traditional peer groups has been a frustrating experience.…”
Section: Wwwmentioning
confidence: 99%